Garantías jurisdiccionales: ¿protección para todos o privilegio para pocos? - Samaniego Quiguiri, Delia Paulina; Urbano Urbano, Pablo Fausto; Días Ledesma, Daniel Fernando; Samaniego Riera, Wilfrido Rodrigo; Martínez Tapia, José David; Navarrete Valladolid, María Isabel; Solis Miranda, Diego Fernando; Murillo Ramos, Franklin Remigio; Pástor Guevara, Juan Carlos; Lara Palomino, María Ana de Jesús (Editorial Grupo AEA, 2026)
Ecuador's judicial system is facing a crisis that questions the effectiveness of jurisdictional guarantees, such as habeas corpus and the right to a fair trial. These tools, designed to protect fundamental rights, have been manipulated by high-profile criminals, thanks to corruption in the judicial system. Recent cases, such as the arrest of judges and police officers in 2024 for collaborating with criminals, show how these guarantees are distorted to provide impunity. The Constitutional Court has pointed out that legal mechanisms, such as the right to medical treatment and due process, have been used to free convicted criminals. This situation has generated a parallel system where citizens' rights are applied unequally, favoring those with resources and connections. Given this reality, it is crucial to reflect on the role of jurisdictional guarantees in Ecuador. Although they are essential for the protection of rights, their abuse raises serious questions about their implementation. This book invites readers to explore the challenges facing the justice system and to propose reforms that strengthen both the guarantees and the judicial system itself. It seeks to ensure that these tools fulfill their mission of protecting the rights of all, promoting a fair and equitable rule of law.